2012
DOI: 10.1016/j.febslet.2012.04.055
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between the disulfide bond formation pathway and cytochrome c maturation in Escherichia coli

Abstract: Highlights► The role of DsbA and DsbD in cytochrome c maturation in E. coli was probed. ► DsbA is not essential for holocytochrome c production. ► DsbD is important but not essential for cytochrome c maturation. ► A model is proposed for cytochrome c biosynthesis in the periplasm of E. coli. ► Heme attachment to and oxidation of the apocytochrome are competing processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…We found that absence of DsbA or DsbB suppresses Ccm deficiency of R. capsulatus CcdA-null [96, 98] or CcmG-null mutants [93], indicating that thioreduction via CcdA-CcmG is dispensable for Ccm in the absence of thio-oxidation by DsbA-DsbB [93]. Similar findings were also shown recently with E. coli [100], reinforcing the proposal that DsbA-DsbB and CcdA-CcmG form a thioredox loop (Fig. 4A).…”
Section: Ccm-system I: Functional Organizationsupporting
confidence: 81%
See 1 more Smart Citation
“…We found that absence of DsbA or DsbB suppresses Ccm deficiency of R. capsulatus CcdA-null [96, 98] or CcmG-null mutants [93], indicating that thioreduction via CcdA-CcmG is dispensable for Ccm in the absence of thio-oxidation by DsbA-DsbB [93]. Similar findings were also shown recently with E. coli [100], reinforcing the proposal that DsbA-DsbB and CcdA-CcmG form a thioredox loop (Fig. 4A).…”
Section: Ccm-system I: Functional Organizationsupporting
confidence: 81%
“…Addition of exogenous thiol compounds is able to alleviate the Ccm deficiency in CcmG and CcdA mutants, confirming their roles in maintaining reduced the apocyt c heme-binding site thiol groups [84, 93, 95, 96]. In the absence of DsbA-DsbB, production of cyts c is decreased but not completely abolished, and in some cases, this can be rescued by addition of oxidants [93, 96100]. We found that absence of DsbA or DsbB suppresses Ccm deficiency of R. capsulatus CcdA-null [96, 98] or CcmG-null mutants [93], indicating that thioreduction via CcdA-CcmG is dispensable for Ccm in the absence of thio-oxidation by DsbA-DsbB [93].…”
Section: Ccm-system I: Functional Organizationmentioning
confidence: 90%
“…The simplest explanation for this observation is that iron chelation is a common component of the Cpx-inducing signal. Disruptions in disulfide bond formation in the periplasm (expected in the presence of diamide, a dsbD mutation, or CuSO 4 [24]) lead to defects in the ligation of iron-containing heme B to apocytochrome c (86)(87)(88). V. cholerae is predicted to have 14 ctype cytochromes in the cell envelope (89).…”
Section: Discussionmentioning
confidence: 99%
“…DsbA has a broad substrate specificity, with an estimated 300 substrates in E. coli (2), and homologs of DsbA appear to be widely distributed among Gram-negative bacteria (1,4). Additional components of the pathway include a disulfide isomerase, DsbC, and its redox partner DsbD (5, 6) as well as a reductase, DsbE (CcmG), that also partners with DsbD and functions to reduce the cysteines in apocytochrome c to enable heme to bind (5,7).…”
mentioning
confidence: 99%